First-ever exploratory study on Mahali ethnomedicine, a blend of diversity and uniqueness of knowledge in utilizing local medicinal flora and fauna (southern West Bengal, India) - Mandal, Suman Kalyan; Saha, Sathi; Rahaman, Chowdhury Habibur (Journal of ethnopharmacology, 2025)
The Mahali is a marginalized ethnic group in eastern India who primarily relies on the local medicinal flora and fauna for their healthcare needs. Their extensive knowledge of medicinal species has largely gone unrecognized for centuries. The forces of modernization and cultural infiltration pose a significant risk of eroding this invaluable treasure of knowledge over time. The present study aimed to document the knowledge of medicinal species used by the Mahali people today, check the status of the existing knowledge in the community, identify the most widely used species in the locality, and figure out how the Mahali people's medicinal knowledge differs from those of other significant ethnic groups in the study area and from earlier published data. Free and prior informed consent (FPIC) was taken from the participants. Ethnomedicinal data were collected through group discussion, semi-structured open-ended question-answer sessions, and walk-in-the-woods. Participant's degree of consensus was checked by Informant agreement ratio (IAR). For identifying frequently used species, the cumulative numerical value of all use reports (UR) for a particular species was considered. A total of 2238 citations were noted for 137 plant taxa, 4 fungal species, and 23 animal species. Altogether 208 folk remedies were recorded for 69 diseases and ailments. The most prevalent health issues were related to skin disorders and digestive complaints. IAR value ranged from 0.89 to 0.95 indicating a higher consensus of using certain medicinal species for specific purposes. Three most useful species were identified as Artemisia nilagirica (C. B. Clarke) Pamp. (UR = 66), Cissus quadrangularis L. (UR = 61), and Asparagus racemosus Willd. (UR = 60). The most frequently cited animal species was Columba livia (Gmelin, 1789) (UR = 23), followed by Odontotermes gurdaspurensis (Holmgren and Holmgren. 1917) (UR = 22), and Varanus bengalensis (Daudin, 1802) (UR = 20). Documenting Mahali's ethnomedicinal knowledge and transforming it into scientific information will be crucial for its preservation, revaluation, and rational application for developing new potential medications. [Display omitted] •Ethnomedicinal knowledge of Mahali ethnic group is recorded first time in India.•The Mahalis utilize 137 plant taxa, 4 fungal species, and 23 animal species as medicine.•13 unique uses including uses of 10 medicinal plants, one medicinal mushroom, and 2 animal species are new addition to the national ethnomedicinal archive.•Therefore, suggestions are offered for more thorough research on Mahali's ethnomedicinal knowledge.